Hepatitis C virus screening and treatment in Irish prisons from nurse managers' perspectives - a qualitative exploration - D. Crowley; M. C. Van Hout; C. Murphy; E. Kelly; J. S. Lambert; W. Cullen (BMC, 2019)
Abstract Background Prisoners carry a greater burden of physical, communicable and psychiatric disease compared to the general population. Prison health care structures are complex and provide challenges and opportunities to engage a marginalised and poorly served group with health care including Hepatitis C Virus (HCV) screening, assessment and treatment. Optimising HCV management in prisons is a public health priority. Nurses are the primary healthcare providers in most prisons globally. Understanding the barriers and facilitators to prisoners engaging in HCV care from the perspectives of nurses is the first step in implementing effective strategies to eliminate HCV from prison settings. The aim of this study was to identify the barriers and facilitators to HCV screening and treatment in Irish prisons from a nurse perspective and inform the implementation of a national prison-based HCV screening program. Methods A qualitative study using focus group methodology underpinned by grounded theory for analysis in a national group of nurse managers (n = 12). Results The following themes emerged from the analysis; security and safety requirements impacting patient access, staffing and rostering issues, prison nurses' skill set and concerns around phlebotomy, conflict between maintaining confidentiality and concerns for personal safety, peer workers, prisoners' lack of knowledge, fear of treatment and stigma, inter-prison variations in prisoner health needs and health service delivery and priority, linkage to care, timing of screening and stability of prison life. Conclusions Prison nurses are uniquely placed to identify barriers and facilitators to HCV screening and treatment in prisoners and inform changes to health care practice and policy that will optimise the public health opportunity that incarceration provides.